Collocations in Malaysian English learners’ writing: a corpus-based error analysis - Ang, Leng Hong; Hajar Abdul Rahim,; Tan, Kim Hua; Khazriyati Salehuddin, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2011)
Although many researchers emphasise that the knowledge of collocations is of great help for language learners to achieve fluency and proficiency, it has been widely recognized that second language learners often have problems with collocations owing to various reasons. This study describes the methods and the results of a corpus-based investigation of the types and sources of verb-noun collocational errors in a subcorpus of a Malaysian learner corpus, EMAS (The English of Malaysian School Students). The corpus consists of 130 essays written by Form Four Malay learners from three different states in peninsula Malaysia. This study was based on the Interlanguage theory and Error Analysis framework was employed to conduct the analysis. Wordsmith Tools software was used to generate the data for this study. To determine the accuracy of collocations, the Oxford Collocations Dictionary and the online British National Corpus (BNC) were referred to. Various types and sources of collocational errors were classified and explained accordingly. The findings of this study indicate that of all seven types of collocational errors, the one occurring most frequently is the preposition-related collocational errors. With regard to the sources of collocational errors, intralingual transfer was found to be the most prominent among the three major categories of sources of collocational errors.